Information and Communication Technologies, a Promising Way to Support Pharmacotherapy for the Behavioral and Psychological Symptoms of Dementia - Piau, Antoine; Rumeau, Pierre; Nourhashemi, Fati; Martin, Maria Soto (Frontiers in Pharmacology, 2019)
Health care systems face an expansion in the number of older individuals with a high prevalence of neurodegenerative diseases and related Behavioral and Psychological Symptoms of Dementia (BPSD). Healthcare providers are expected to develop innovative solutions to follow-up patients over time in the community. To date, we are unable to continuously and accurately monitor the nature, frequency, severity, progression and response to treatment of BPSD after the initial assessment. Technology could address this need and provide more sensitive, less biased and more ecologically valid measures. This could provide an opportunity to re-evaluate therapeutic strategies more quickly and, in some cases, to treat earlier, when symptoms are still amenable to therapeutic solutions. Several studies confirm the relationship between sensor-based data and cognition, mood and behavior. Most scientific work on mental health and technologies supports digital biomarkers, not so much as diagnostic tools but rather as monitoring tools, an area where unmet needs are significant. In addition to the implications for clinical care, these real-time measurements could lead to the discovery of new early biomarkers in mental health. Many also consider digital biomarkers as a way to better understand disease processes, and that they may contribute to more effective pharmaceutical research by (i) targeting the earliest stage, (ii) reducing sample size required, (iii) providing more objective measures of behaviors, (iv) allowing better monitoring of noncompliance, (v) and providing a better understanding of failures. Finally, communication technologies provide us with the opportunity to support and renew our clinical and research practices.